2015
DOI: 10.4250/jcu.2015.23.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Clinical Behavior of Hypertrophic Cardiomyopathy in a Latin American Cohort in Contrast to Cohorts from the Developed World

Abstract: BackgroundHypertrophic cardiomyopathy (HCM) is the most common hereditary heart disease with diverse phenotipyc, genetic expession and clinical presentations. The evolution of patients with HCM in Latin America has not been properly described being the frequency, the long-term prognosis as well as the predominant phenotypic expression still unknown. The aim of this study was to determine the survival rate of HCM patients having different phenotypes in a Mexican cohort of patients.MethodsClinical and echocardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…16 LVEF in concentric HCM was higher than other types of HCM in present study (72.30%), whereas LVEF in asymmetric septal HCM was higher in a study by Espinola-Zavaleta (67%). 17 The values found in this study was significant among the cardiac phenotypes of HCM.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…16 LVEF in concentric HCM was higher than other types of HCM in present study (72.30%), whereas LVEF in asymmetric septal HCM was higher in a study by Espinola-Zavaleta (67%). 17 The values found in this study was significant among the cardiac phenotypes of HCM.…”
Section: Discussionsupporting
confidence: 52%
“…Espinola-Zavaleta et al found the interventricular septal thickness in concentric HCM was lower than asymmetric septal HCM. 11 However, we found that in our study population interventricular septal thickness this two group was almost similar. The overall value observed in this study was similar to that of the other reviews.…”
Section: Discussionmentioning
confidence: 43%
“… 93 For hypertrophy between 13 and 14 mm, other factors, such as family history, specific ECG changes, symptoms, another imaging method and even genetic evaluation should be considered in the differential diagnosis. 94 In first-degree relatives of a HCM patient, hypertrophy greater than 13 mm is also highly indicative of this disease. 91 Hypertrophy related to pressure overload, physical training and basal septal hypertrophy in the elderly should be considered in the differential diagnosis.…”
Section: Individuals With Cardiomyopathies and Myocarditismentioning
confidence: 99%
“…HCM is an often under-diagnosed disease 7 , with an estimated prevalence of approximately 1/500 of the general population. It is equally present in both men and women, and can affect any age group 8 , 9 .…”
Section: Introductionmentioning
confidence: 99%